TEACHERS' AND STUDENTS' PERCEPTIONS AND THE VARIABLES THAT IMPACT THE PERCEPTIONS OF USING THE ENGLISH CONVERSATION PRACTICE APPLICATION IN SPEAKING CLASS - Putra, Komang Bayu Widhyasmara; Ramendra, Dewa Putu; Utami, I G A Lokita Purnamika (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2023)
The advancement of technology has positive impacts on education. This study aims to identify teachers' and students' perceptions and the variables that impact EFL teachers' and learners' perceptions of using the English Conversation Practice application in speaking class. This study involved thirty-three pupils and three English teachers from SMK Negeri 1 Gianyar, who were chosen using the purposive sampling technique. The data were collected through interviews and observation and analyzed using the interactive data analysis model. The study results show that the students and teachers positively perceive implementing the 'English Conversation Practice' application in speaking class. Besides, the variables that impact EFL teachers' and learners' perceptions of the use of the English Conversation Practice application in speaking class were that the application gave them a new experience in learning to speak, it is simple to use, it does not require a large internet quota, and it allows for the flexibility of learning at any time and in any location. Thus, considering the study's results, it is recommended that EFL teachers use the Conversation Practice application in their speaking class.